Paciente femenino de 5 años de edad con diagnóstico de bronquitis aguda. - Suarez Rodríguez, Odalys Anthonella (2021)
Acute bronchitis is a disease that produces inflammation of the bronchi, mucous membranes of the acute type. Generally associated with respiratory tract infections and these are caused mostly by viruses, the incidence of this condition occurs more in the winter season and affects mainly children. In this case, we will see a 5-year-old female patient who arrived at the hospital emergency area with a febrile clinical picture (38ºC) caused by a productive cough of 15 days of evolution, initial rhinorrhea, she underwent physical examinations to which Upon auscultation, she presented bilateral wheezing disseminated on expiration without respiratory distress, for which she evaluated bronchial inflammatory disorder, which led to a diagnosis of acute bronchitis without admission criteria and she was referred for outpatient treatment. Acute bronchitis is the fifth leading cause of disease in the lower airways in children under 5 years of age, it is also one of the most common causes of consultation in hospitals and one of the most common diagnoses in primary care centers and in emergency services and pediatric areas.